Research on risk evaluation of agricultural supply chain finance based on Grey–DEMATEL–ISM - Zhou, Xi; Yang, Chuang; Ye, Peijie; Zhang, Peicheng (Frontiers in Sustainable Food Systems, 2025)
In recent years, under the background of digital technology, agricultural supply chain finance (SCF) has ushered in new development opportunities and become an important lever to promote the development of the agricultural industry and achieve the goal of rural revitalization. Rapid and accurate risk assessment of agricultural supply chain finance can provide strong support for its sustainable development and agricultural production. This study selected 12 risk evaluation indicators and constructed a risk evaluation index system from four dimensions: industry risk, the credit risk of small- and medium-sized enterprises, core enterprise status, and supply chain operation status. Using the Grey–DEMATEL model to analyze the impact relationships and pathways among risk factors and identify key influencing factors. Combined with the ISM method, the comprehensive impact matrix and reachability matrix are obtained, and a hierarchical structure model of risk factors is established. To verify the effectiveness of the risk assessment method, D company was selected as the research object, and the constructed risk control model was applied to D company. Based on the results, strategies for preventing and controlling financial risks in the agricultural product supply chain are proposed from the aspects of enterprise credit risk prevention and control, establishment of digital platforms, and standardization of supply chain processes. Based on the Grey–DEMATEL–ISM model, effective evaluation of financial risks in agricultural product supply chains can be conducted.